(3aUhU GdaUhd hYbhO GdYbhds - (3gHI Gddg Hf LYaQ Hf SfGA Gdedc, CHh GdbGSe GHf SfGA Gdedc GdeUQj,J (B608 (3g` s
(3ChdgG (B:s
(3hgPG cJGH dG fGbI dj ajg hdG Led hdG EYeGd hdG Yed hdG TcQ hdG MeO s
(3BNQgG (B:s
(3hCdHSfj MdjgG hMddgG hUdhGJg Ydi eMeO GdfHj s
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdis
(3fSNI KGfjI hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B71 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B135 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B506s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B192 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B93 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs